The effects of COVID-19 pandemic on women's access to maternal health and family planning services in Egypt: an exploratory study in two governorates - Nahla Abdel Tawab; Salma A. Tayel; Sally M. Radwan; Mohamed A. Ramy (BMC, 2024)
Abstract Background The COVID-19 pandemic has been noted to decrease access to maternal health and family planning services globally. However, evidence from the Middle East and North Africa region is very scarce and limited. We qualitatively explored women's experiences in accessing maternal health and family planning services during the COVID-19 lockdown months in the two Egyptian governorates of Port Said and Souhag. Methods Using a case study design, semi-structured phone interviews were conducted with a total of 40 women aged 18-35 years from Port Said and Souhag governorates in Egypt. Interviews explored women's experiences in accessing maternal health and family planning services during COVID-19 lockdown months, their coping strategies, and impact of challenges and/or coping strategies on participants and their families. The collected data was analyzed manually using qualitative thematic analysis. Results Many participants were unable to access maternal health and family planning services during COVID-19 lockdown due to fear of contracting the virus, closure of health facilities, changing service hours, family planning method or drug stock-outs, and/or financial constraints. The above challenges in accessing services along with coping strategies that some women and their families used exposed women to additional health risks, including unintended pregnancies, and posed several social, emotional, and financial burdens to many. Conclusions The COVID-19 pandemic and associated lockdown measures undermined women's access to maternal and family planning services and interfered with their ability to achieve their reproductive goals. The paper concludes with a number of recommendations to ensure access to maternal and family planning services at times of crisis. Those recommendations include: (1) adapting reliable guidelines from humanitarian settings, (2) providing adequate guidance to healthcare providers and the public to tackle fears and misinformation, (3) making self-care products available such as oral contraceptive pills, vaginal rings and self- administered injectables, (4) involving other health professionals in the provision of maternal and family planning services through task-sharing/shifting, (5) expanding the use of telemedicine and/or digital health services especially to those living in remote areas and (6) raising policymakers' awareness of the centrality of reproductive rights and the importance of protecting them at all times.